The association between socio-economic indicators and the cantonal sports performance in the National Sport Games Costa Rica 2016 - Chacón Araya, Yamileth (2018)
The aim of the study was to determine the association between economic and social indicators and their predictive value for cantonal sports performance in athletes who participated in the 35th National Sport Games 2016 in San José, Costa Rica. Each canton was ranked according to the total medals obtained during the games and correlations were computed with the socio-economic indicators human development index (HDI), human poverty index (HPI), life expectancy index (LEI), knowledge index (KI), material well-being index (MWI), HDI related to gender (GDI), and gender empowerment measure (GEM). Spearman Rho bivariate correlations and a multiple lineal regression were used to analyze data. Significant associations were found between the cantonal position in the Games and the HDI (rρ = 0.307, p = 0.005), GDI (rρ = 0.316, p = 0.004), GEM (rρ = 0.326, p = 0.003), HPI (rρ = - 0.310, p = 0.005), MWI (rρ = 0.335, p = 0.002); however, non-significant correlations were found for LEI (rρ = 0.144, p = 0.201) and KI (rρ = 0.335, p = 0.231). Multiple linear regression analysis revealed that GDI (β = 0.268; p = 0.016) was the only predictive variable that entered in the model, explaining 7.2% of the variance in the total number of medals. In conclusion, although various socio-economic indicators were associated with sport performance, only the HDI related to gender was the most important predictor. More attention should be given to factors that gender equality in the different cantons, as it has an association with sport success.